Intellectual Triumph in The Islamic Scientific Exploration of Andalusia - Zaldi Zaldi; M. Iqbal Irham; Sugeng Wanto (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2023)
This article delves into the period of Islamic magnificence in Andalusia, spanning from 913 to 961 CE, under the rule of Khalifah Abdurrahman An-Nashir. It sheds light on the epoch's remarkable strides in scientific exploration, notably through the prominence of influential scholars and scientists like Ibn Rushd and Ibn Athiyyah, whose enduring contributions continue to resonate within the Islamic world. Methodologically, this research adopts a historical approach, meticulously examining pertinent books and journals to unearth the narrative of this transformative era. This study showed that central to this era's intellectual ascendance was the establishment of comprehensive educational institutions, ranging from foundational to advanced levels. A striking exemplar is the University of Cordoba, a revered seat of learning that exemplifies an integrated educational approach. Additionally, the era's scientific vitality found material expression in the creation of opulent libraries, housing collections exceeding a million scholarly volumes. The outcome of this exploration underscores the palpable intellectual dynamism that characterized the Islamic golden age in Andalusia under Khalifah Abdurrahman An-Nashir's leadership.